Phosphorus in farm roadway substrates: contrasting spatial and temporal patterns in dairy and beef farms - Sifundza, Lungile Senteni; Murnane, John G.; Daly, Karen; Lopez-Sangil, Luis; Leach, Simon; Tuohy, Patrick; Cardiff, John; Fenton, Owen (Frontiers in Environmental Science, 2024)
The mobilisation and impact of roadway runoff on dairy farms has been established as a sub-component of the nutrient transfer continuum. It is acknowledged that fresh nutrient sources deposited on roadways dominate runoff and recent work has shown that available phosphorus (P) in roadway substrates is also an important source component. The objectives of this study were to understand spatial and temporal available P concentrations in roadway substrate (aggregate and soil mix) across dairy and beef farms during the open (February–October, when cows use the roadway network and fields) and closed (November–January, when cows were housed) periods and identify locations which could be considered critical source areas (CSA). For the study, roadway substrate samples were taken at 18 locations on each farm, across 8 sampling periods, and were analysed for available P. Results showed that mean available P concentrations (Morgan’s P) in the sampling locations ranged from 15.9 to 101.4 mg L-1 for the Dairy Farm, from 4.1 to 59.4 mg L-1 for Beef Farm 1 and from 6.3 to 23.2 mg L-1 for Beef Farm 2. In open period, the results showed that mean available P concentrations were 75.4±30.9, 14.9±3.2 and 13.4±2.5 mg L-1 for the Dairy Farm, Beef Farm 1 and Beef Farm 2, respectively. In closed period, the mean available P were 40.3±17.2, 10.4±1.0 and 9.8±0.2 mg L-1 for Dairy Farm, Beef Farm 1 and Beef Farm 2, respectively. Overall, P concentrations on the Dairy Farm roadways was up to 4 times greater than that in the Beef Farms’ roadways. Compared to soils in adjacent fields, P concentrations in the Dairy and Beef Farms roadways was up-to 7 and 2 times higher, respectively. Critical roadway sections that required mitigation were two in the Dairy Farm, one in Beef Farm 1 and two in Beef Farm 2. In addition to fresh faeces and urine (i.e. dominant source of nutrients in farm roadways), this study showed that nutrient enriched roadway materials are a labile P source. Thus future mitigation of roadway runoff must consider all roadway nutrient sources, including livestock fresh excreta as well used roadway surface materials